The orphan's tale ebook A novel. - Jenoff, Pam (2017)
Look for Pam Jenoff's new novel, The Woman with the Blue Star, an unforgettable story of courage and friendship during wartime. A New York Times bestseller! "Readers who enjoyed Kristin Hannah's The Nightingale and Sara Gruen's Water for Elephants will embrace this novel. " —Library Journal "Secrets, lies, treachery, and passion.... I read this novel in a headlong rush." —Christina Baker Kline, #1 New York Times bestselling author of Orphan Train A powerful novel of friendship set in a traveling circus during World War II, The Orphan's Tale introduces two extraordinary women and their harrowing stories of sacrifice and survival. Sixteen-year-old Noa has been cast out in disgrace after becoming pregnant by a Nazi soldier and being forced to give up her baby. She lives above a small rail station, which she cleans in order to earn her keep... When Noa discovers a boxcar containing dozens of Jewish infants bound for a concentration camp, she is reminded of the child that was taken from her. And in a moment that will change the course of her life, she snatches one of the babies and flees into the snowy night. Noa finds refuge with a German circus, but she must learn the flying trapeze act so she can blend in undetected, spurning the resentment of the lead aerialist, Astrid. At first rivals, Noa and Astrid soon forge a powerful bond. But as the facade that protects them proves increasingly tenuous, Noa and Astrid must decide whether their friendship is enough to save one another—or if the secrets that burn between them will destroy everything. Don't miss Pam Jenoff's new novel, Last Twilight in Paris, a gripping mystery and an unforgettable story about love and survival. Read these other sweeping epics from New York Times bestselling author Pam Jenoff: Code Name Sapphire The Lost Girls of Paris The Woman with the Blue Star The Ambassador's Daughter The Diplomat's Wife The Last Summer at Chelsea Beach The Kommandant's Girl The Winter Guest